Structural-typological Approach to the Analysis of Civic Identity - Petrovska, Inha (Psychological Prospects Journal, 2016)
The article presents suggestions of using structural and typological approach to the formation of civic identity evaluation. The importance of in-depth analysis of cognitive, emotional and evaluative features and behavioral figurative semiotic components of civil identity population of all ages and with varying regional identity is noted. Analysis of civil identity as a social and multifaceted psychological phenomena is also connected with application of constructive approach, since this approach in the context of civic identity can be regarded as a dynamic system constructs, which is focused on representation citizen rights, accompanied by estimate and semantic manifestations. It is proved that the growth of Ukrainian civil identity formation increases the desire not to change the place of residence (and remain in Ukraine) even where possible, educate their children in Ukrainian educational institutions, honestly perform a civic duty to work for the good of Ukraine. The higher the formation level of Ukrainian civic identity, the more citizens aimed at limiting the actions and motives which may harm others and violate social expectations and norms, the more they focus on stability, security and harmony of society, family and himself, the more they focus on maintaining and improving the welfare of people that are in constant contact; the more they aim to realise their abilities and achieve personal success by means of manifestation of competence in their country. Different types of civil identity were revealed, namely “patriotic”, “uncertain”, “protest”, the existence of “conflict / non-conflict” and “indifferent” types are assumed. Ukrainian civic identity in the perception of citizens is associated with patriotism, active citizenship, personal and professional opportunities in the implementation of the state.Keywords: identification, civic identity, state, patriotism, citizenship.